Komparasi Efektifitas Model Group Investigation Dan Children Learning In Science Terhadap Pembelajaran Siswa Kelas IV SD - Inul Arnadi; Cayati Cayati; Siti Nurul Haliza; Eka Fitriana HS (Departement of Mathematics Education, 2024)
This research was conducted to determine the comparison between the group investigation model and children learning in science on science learning for fourth grade students at SD Inpres Moncong-Moncong. This research uses a quantitative approach with the type of experimental research and research design, namely (nonequivalent control group design) with class IV A consisting of 20 students and IV B consisting of 21 students using simple random sampling, the research instruments used are observation sheets, questionnaires and tests learning outcomes, as well as data collection techniques consisting of observations, questionnaires and tests which are reviewed from students' science learning. After analyzing the data, researchers found differences in effectiveness between the group investigation model and children learning in science through three indicators of effective learning, namely for student activities in the group investigation model 3.8 (very good) while for the children learning in science model 3.7 ( very good), the student response for the group investigation model was 3.4 (good) while for the children learning in science model it was 2.8 (good) and the learning outcomes for the group investigation model were 3.6 (very good) while the children learning in science model was 3, 1 (good). So, through the results of the data analysis that has been carried out, it can be concluded that the group investigation model has proven to be very effective in terms of science learning for students at SD Inpres Moncong-Moncong with a score of 3.5 (very effective) while the children learning in science model gets a score of 3.1 (quite effective). Keywords: Group Investigation Model, Children Learning In Science, and Science Learning